2012
DOI: 10.1017/s1047951112001163
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin I after cardiopulmonary bypass in infants in comparison with older children

Abstract: AbstractObjectiveAt the present time, there is a trend towards performing open heart surgery at a younger age. Myocardium of infants has been thought to be more vulnerable to cardiopulmonary bypass in comparison with adults. For this study, we evaluated the degree of myocardial injury by measurement of cardiac troponin levels in infants in comparison with older children for similar surgeries. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
0
15
2
Order By: Relevance
“…There have been conflicting reports of whether peak TN-I levels are associated with poor surgical outcomes. 9,18,19 Our study did not reveal significant correlation between peak TN-I level and outcomes. In addition, individual TN-I levels varied widely at each time point even within the individual surgical groups, such that no particular TN-I level could be reliably used to predict poor clinical outcome.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…There have been conflicting reports of whether peak TN-I levels are associated with poor surgical outcomes. 9,18,19 Our study did not reveal significant correlation between peak TN-I level and outcomes. In addition, individual TN-I levels varied widely at each time point even within the individual surgical groups, such that no particular TN-I level could be reliably used to predict poor clinical outcome.…”
Section: Discussioncontrasting
confidence: 72%
“…16,17 Previous studies have indicated that infants tend to have higher troponin leak following myocardial damage when compared with older children, and for this reason we narrowed the scope of our cohort to infants younger than 1 year of age. 18 The two major intraoperative factors that correlated with increased postoperative TN-I levels were: (1) the use and duration of CPB, and (2) the requirement of ventricular incision during surgery ( Figure 2). Under ideal circumstances, one would like to establish expected range of post-operative, time-varying troponin levels for every specific procedure.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently studies pointed out that high troponin levels were not associated with high cardiovascular risk or mortality in infants who underwent congenital cardiac surgery (16,17) .…”
Section: Discussionmentioning
confidence: 98%
“…[12,13] Correlation between the levels of plasma troponin I higher than 100 µg/L after CPB in children and postoperative mortality has been put forward. [12][13][14] In pediatric cardiac surgery, surgical interventions may require ventricular incision and myocardial resection, which increases postoperative CK-MB and troponin I levels. Therefore, obtaining samples for myocardial damage indicators during similar operations is important to provide homogeneity.…”
Section: Discussionmentioning
confidence: 99%